Implementasi Load Balancing Menggunakan Metode PCC (Per Connection Classifier) Pada Yayasan Bina Jaya Palembang - Firlyan Kelvin Saiputra; Aan Restu Mukti (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
Abstract The need for internet services and computer networks today is very important often with technological advances. Therefore, proper and reliable design is needed in building a good network quality. One of the practical and appropriate solutions that can be applied in overcoming the progress of data communication is by distributing load balancing workloads. So far, there are still many people who think wrong about load balancing, that by using load balancing two connection lines, the bandwidth that will be obtained will be double the bandwidth before using load balancing or in other words the accumulation of the two bandwidths. Load balancing is a concept that is useful for balancing the load or load on the network infrastructure. In a load balancing system, the load sharing process has its own method and algorithm. Per Connection Classifier is one method that can be used in load balancing, Per Connection Classifier can be used to group connection traffic through or out of the router into several groups. For this reason, load balancing is implemented using the Per Connection Classifier method at the Bina Jaya Palembang Foundation in an effort to group connection traffic through or out of the router into several groups. Keywords—Implementation, Load Balancing, Per Connection Classifier